2023
DOI: 10.3390/ani13182946
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change and Heat Stress on Milk Production in Korean Holstein Cows: A Large-Scale Data Analysis

Eunjeong Jeon,
Seungho Jang,
Joon-Mo Yeo
et al.

Abstract: This study investigated the effects of heat stress on milk production in Korean Holstein cows using large-scale data. Heat stress was assessed using the temperature-humidity index (THI). Weather records (2016 to 2020) were collected from 70 regional weather stations using an installed automated surface observing system (ASOS). A dataset of 2,094,436 milk production records from 215,276 Holstein cows obtained from the Dairy Cattle Genetic Improvement Center was analyzed. Stepwise selection was used to select th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Milk production was not influenced by season nor by the type of CL. Although no specific meteorological measurements were taken during the study, this result is surprising, as lower milk yields are usually reported in dairy cattle studies during elevated ambient temperatures in summer [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 88%
“…Milk production was not influenced by season nor by the type of CL. Although no specific meteorological measurements were taken during the study, this result is surprising, as lower milk yields are usually reported in dairy cattle studies during elevated ambient temperatures in summer [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 88%
“…According to the research of several authors [26,[28][29][30], the risk of HS occurs when THI values exceed 68 or 72. According to Jeon et al [31], it is more accurate to study the influence of the maximum values of the THI (THI_max) on the quantity and quality of milk.…”
Section: Discussionmentioning
confidence: 99%